2016
DOI: 10.1038/srep31467
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physical properties of the dust particles in Qatar and their influence on the PV panel performance

Abstract: Recently, extensive R&D has been conducted, both by industry and academia, to significantly raise the conversion efficiency of commercial photovoltaic (PV) modules. The installation of PV systems aimed at optimizing solar energy yield is primarily dictated by its geographic location and installation design to maximize solar exposure. However, even when these characteristics have been addressed appropriately, there are other factors that adversely affect the performance of PV systems, namely the temperature-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 23 publications
7
39
0
1
Order By: Relevance
“…Qatar, located in the sun belt region of the world, receives about 9.4 h of sunshine daily and consequently receives a high amount of UV radiation [25,26]. It is also within the global dust belt, and thus, its atmosphere constantly has a large proportion of mineral desert dust aerosol particles that mostly absorb UV radiation [25,27]. Most of its mineral dust concentrations come through two wind regimes-the summer and the winter Shamal winds that blow from the deserts of Iraq, Syria, and the Arabian Peninsula [21,24].…”
Section: The Region Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Qatar, located in the sun belt region of the world, receives about 9.4 h of sunshine daily and consequently receives a high amount of UV radiation [25,26]. It is also within the global dust belt, and thus, its atmosphere constantly has a large proportion of mineral desert dust aerosol particles that mostly absorb UV radiation [25,27]. Most of its mineral dust concentrations come through two wind regimes-the summer and the winter Shamal winds that blow from the deserts of Iraq, Syria, and the Arabian Peninsula [21,24].…”
Section: The Region Of Interestmentioning
confidence: 99%
“…The LER accounts for ground surface reflectance as well [35]. While a number of studies on UVI with satellite measurements have used LER of less than 0.1 to identify clear sky days [27,30], Qin et al, 2019, Herman et al, 2013, and O'Byrne et al 2013, showed that OMI LER over the Arabian desert region is higher due to higher surface reflectance of the desert [33,35,36]. Therefore, for this study over the Arabian Desert region, LER of less than 0.2 is used to represent clear sky days.…”
Section: Satellite-derived Uvi From Omi Auramentioning
confidence: 99%
“…Recently, several works have reported on the characterization of airborne particulate matter in this area [11][15] [16], but there is considerable lack on the identification of the sources of these particles [12] [14]. Aissa et al [16] had characterized dust samples collected in Doha-Qatar during the summer. It was found that calcite dominates the dust composition with 58% atomic content.…”
Section: Introductionmentioning
confidence: 99%
“…A large market for photovoltaics (PV) and concentrated solar power (CSP) using mirrors is to be located in desert regions: while these regions represent more than 30% of the total earth land surface, the annual solar energy in such regions is typically two times higher than the average annual radiation in central Europe. The major limitation for PV electricity production in desert is the soiling due to sandstorm and dust accumulation at the PV module surface, which can reduce the power output of a power plant by up to 28% in only 7 days, thus requiring frequent cleaning of the surface of the PV modules or CSP mirrors.…”
Section: Introductionmentioning
confidence: 99%